Spirituality for EAPI: Forming Pastoral Servants with Discerning Hearts - Machado, Francisco (Archīum Ateneo, 2020)
This paper articulates how the East Asian Pastoral Institute (EAPI) understands and seeks to foster spirituality. The ideas expressed here are the author’s attempt to convey his own understanding of what good spirituality is and of how EAPI can foster it among its participants. After an introduction about the relevance of spirituality for the formation of pastoral workers, a general definition of spirituality is given. This is followed by a reflection on how some key elements typical of the Asia Pacific context can and should affect our spirituality. The central idea explored in the rest of the paper is that of spiritual maturity. This notion is defined and explained by means of a model which articulates how spiritual growth happens in stages. The author then suggests concrete characteristics proper of the spiritually mature person and gives ideas on how the EAPI formative context can help participants develop these aspects of maturity. Finally, it is argued that discernment can be seen as the central characteristic which makes it possible for pastoral workers to truly become servants of God’s Kingdom in today’s word.